2001
DOI: 10.1155/s1064744901000242
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter Study of Bacterial Vaginosis in Women With orat Risk for Human Immunodeficiency Virus Infection

Abstract: Background: Bacterial vaginosis is a common gynecologic infection that has been associated with a variety of gynecologic and obstetric complications, including pelvic inflammatory disease, postabortal infection and premature delivery. Recent studies suggest that bacterial vaginosis may increase a woman’s risk for human immunodeficiency virus (HIV). We undertook this study to assess whether the prevalence and characteristics of bacterial vaginosis differed according to HIV status in high-risk US women

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(30 citation statements)
references
References 34 publications
5
24
1
Order By: Relevance
“…Also at lower CD4 cell counts, the LGTI are more severe and less susceptible to treatment [7]. Similar results were obtained in the study by Warren et al with the prevalence of bacterial vaginosis to be 47 % in the HIV-positive women compared with 44 % in the HIV-negative women, and among HIV-positive women, they concluded that the use of antiretroviral drugs was associated with a lower prevalence of bacterial vaginosis [4]. Goel et al found the prevalence of bacterial vaginosis to be 30 %, mixed infection 30 %, and candidiasis 10 % among HIV-seropositive women.…”
Section: Trichomoniasis and Hivsupporting
confidence: 76%
See 2 more Smart Citations
“…Also at lower CD4 cell counts, the LGTI are more severe and less susceptible to treatment [7]. Similar results were obtained in the study by Warren et al with the prevalence of bacterial vaginosis to be 47 % in the HIV-positive women compared with 44 % in the HIV-negative women, and among HIV-positive women, they concluded that the use of antiretroviral drugs was associated with a lower prevalence of bacterial vaginosis [4]. Goel et al found the prevalence of bacterial vaginosis to be 30 %, mixed infection 30 %, and candidiasis 10 % among HIV-seropositive women.…”
Section: Trichomoniasis and Hivsupporting
confidence: 76%
“…There is a complex interaction between HIV infection and LGTI. Many studies have shown increased prevalence, incidence, and severity of LGTI in HIV-seropositive women [4][5][6][7],while a few studies reported no differences in prevalence of LGTI in the HIV-infected and non-HIV-infected women of reproductive age group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15 In a study by Warren et al on 854 HIV positice and 434 HIV negative women, it was found that prevalence of Bacterial Vaginosis was 47 % in HIV positive as compared to 44% in HIV negative women ; this difference was not statiscally significany ( P=0.36). 19 In present study HIV positive patients showed more prevalence of Candidiasis (28%), Trichomoniasis (28%), Herpes ( 30%) followed by HPV (14%)and Chlamydia (8%). But in HIV positive patients with Bacterial Vaginosis prevalence of above infections was more i.e Candidiasis (33.33%) , Trichomoniasis (33%) , Herpes (38.85%), HPV (22.22%).In consort and control group patients with Bacterial Vaginosis most common co-infection was of Trichomoniasis.This correlate well with study done in STD clinic in Seattle in which 75% of women with trichomoniasis also had Bacterial Vaginosis compared with 47% of women without Trichomoniaisis ( P <0.001).…”
Section: Discussionsupporting
confidence: 49%
“…African women also tend to have significantly higher vaginal pH than do Caucasian women . In addition, the prevalence of BV has been shown to be higher in HIV-infected women compared to HIVuninfected women (Sewankambo et al, 1997;Jamieson et al, 2001;Warren et al, 2001). From the foregoing information, it is apparent that more studies are needed to complete our understanding of BV in affected subpopulations.…”
Section: Introductionmentioning
confidence: 99%